The Influence of Work Environment on Employee Motivation and Performance in The Health Service Sector - Firdaus Firdaus; Hasbi Basith Sukarno; Ardi Taryanto (ABISATYA DINAMIKA ISWARA, 2026)
Employee performance is one of the key factors determining the success of improving the quality of healthcare services. However, the influence of the work environment on performance is not always direct, as psychological factors can potentially mediate this relationship. One factor thought to play a significant role is work motivation. This study aims to analyze the influence of the work environment on employee performance and examine the role of work motivation as a mediating variable in healthcare organizations in Indonesia. This study employed a quantitative approach with an explanatory research design. Data were collected through questionnaires distributed to 73 respondents, consisting of medical personnel, paramedics, and administrative staff, using a total sampling technique. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test direct and indirect relationships between variables. The results showed that the work environment has a positive and significant influence on both work motivation and employee performance. Furthermore, work motivation proved to have the greatest influence on employee performance and served as a mediating variable in the relationship between the work environment and performance. These findings indicate that performance improvement in healthcare organizations is influenced not only by the conditions of the work environment but also by the level of motivation of each individual. This study concludes that work motivation is a psychological mechanism that plays a crucial role in explaining the relationship between the work environment and employee performance. Therefore, strategies to improve employee performance need to be directed at managing a conducive work environment that can encourage and sustain work motivation.